2016
DOI: 10.1002/oby.21357
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat restriction increases fat taste sensitivity in people with obesity

Abstract: ObjectiveIndividuals with obesity may be less sensitive to the taste of fat, and it is hypothesized that this is due to excess dietary fat intake. This study assessed the effect of a 6‐week low‐fat (LF) or portion control (PC) diet matched for weight loss on fat taste thresholds, fat perception, and preference in people with overweight/obesity.MethodsParticipants (n = 53) completed a randomized dietary intervention and consumed either a LF diet (25% fat) or PC diet (33% fat) for 6 weeks. Fat taste thresholds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 22 publications
3
62
0
1
Order By: Relevance
“…It is widely believed that the human taste system consists of five basic tastes: sweet, sour, salty, bitter, umami, and much recent evidence supports a sixth taste responsive for fatty acids (Chalé‐Rush, Burgess, & Mattes, ; Mattes, , ; Newman, Haryono, & Keast, ; Newman, Bolhuis, Torres, & Keast, ; Newman & Keast, ; Running, Craig, & Mattes, ; Stewart & Keast, ; Stewart et al., ; Stewart, Feinle‐Bisset, & Keast, ; Tucker, Edlinger, Craig, & Mattes, ). More recent psychophysical studies suggest that humans may perceive complex carbohydrates, independent of sweet taste (Lapis, Penner, Balto, & Lim, ; Lapis, Penner, & Lim, , ; Low, Lacy, McBride, & Keast, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that the human taste system consists of five basic tastes: sweet, sour, salty, bitter, umami, and much recent evidence supports a sixth taste responsive for fatty acids (Chalé‐Rush, Burgess, & Mattes, ; Mattes, , ; Newman, Haryono, & Keast, ; Newman, Bolhuis, Torres, & Keast, ; Newman & Keast, ; Running, Craig, & Mattes, ; Stewart & Keast, ; Stewart et al., ; Stewart, Feinle‐Bisset, & Keast, ; Tucker, Edlinger, Craig, & Mattes, ). More recent psychophysical studies suggest that humans may perceive complex carbohydrates, independent of sweet taste (Lapis, Penner, Balto, & Lim, ; Lapis, Penner, & Lim, , ; Low, Lacy, McBride, & Keast, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, such inferences would need to be confirmed in an adequately powered trial. Interestingly, exposure to low-fat diets (4-6 wk) has been shown to significantly increase fat taste sensitivity among lean and overweight or obese individuals and increase liking or preference for some low-fat foods (Stewart and Keast, 2012;Newman et al, 2016). Further research is warranted to investigate whether repeated exposure could increase consumer acceptance of FA-modified foods, such as dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of a low fat diet was associated with lower thresholds for lean and obese participants. An additional trial reported that dietary energy restriction for 6 weeks in obese adults led to lower fat detection thresholds, but this did not differ with dietary fat composition [66].…”
Section: Recent Dietmentioning
confidence: 97%
“…However, the authors note that individuals with obesity were present in all categories of taste responsiveness (i.e., 8, 3, 3, 2 individuals in the low to high performance quartiles). Six weeks of energy restriction in individuals who were overweight or obese led to improved fat ranking accuracy relative to baseline when the diet was lower in fat, but not when energy restriction only entailed reduced portion sizes [66]. However, no comparison between the two diet groups was reported precluding assessment of a BMI effect.…”
Section: Bmimentioning
confidence: 99%